2020
DOI: 10.1136/jitc-2020-000785
|View full text |Cite
|
Sign up to set email alerts
|

Combined DLL3-targeted bispecific antibody with PD-1 inhibition is efficient to suppress small cell lung cancer growth

Abstract: BackgroundSmall cell lung cancer (SCLC) accounts for 15% of lung cancers, and the primary treatment of this malignancy is chemotherapy and radiotherapy. Delta-like 3 (DLL3) is an attractive target for SCLC immunotherapy since its expression is highly restricted to SCLC with a neglectable appearance on normal adult tissues. In the current study, we aimed to explore the efficacy of DLL3-targeted SCLC immunotherapy via the engagement of T cell.MethodsAs a proof of concept, we constructed DLL3-targeted bispecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…On the other hand, Chen and colleagues introduced delta-like 3 (DLL3) as an attractive target for the treatment of small cell lung cancer (SCLC). They showed that DLL3 targeted with antibody and CAR-T cell alone or along with PD-1 inhibition kill DLL3 tumor cells including H82, H196, and H446 cell lines [96].…”
Section: Lung Cancermentioning
confidence: 99%
“…On the other hand, Chen and colleagues introduced delta-like 3 (DLL3) as an attractive target for the treatment of small cell lung cancer (SCLC). They showed that DLL3 targeted with antibody and CAR-T cell alone or along with PD-1 inhibition kill DLL3 tumor cells including H82, H196, and H446 cell lines [96].…”
Section: Lung Cancermentioning
confidence: 99%
“…Engineered cell-based therapies for lung cancer have so far been designed to target epidermal growth factor receptor (EGFR) and variant III (EGFRviii), glypican 3 (GPC3), human epidermal growth factor receptor 2 (HER2), Protein tyrosine kinase 7 (PTK7), erythropoietin-producing hepatocellular carcinoma A2 (EphA2), mesothelin (MSLN), prostate stem cell antigen (PSCA), mucin 1 (MUC1), carcinoembryonic antigen (CEA), natural killer group 2D (NKG2D), tyrosine kinase-like orphan receptor 1 (ROR1), and programmed cell death ligand 1 (PD-L1),lung-specific X (LunX), and delta-like 3 (DLL3) (101)(102)(103)(104).…”
Section: Cellular Therapy In Lung Cancermentioning
confidence: 99%
“…C600952-0501; Sangon Biotech Co., Ltd; Shanghai, China). The purity of the preparations was analyzed by SDS-PAGE (31).…”
Section: Preparation Of Recombinant B7-h4 Proteinsmentioning
confidence: 99%